THE RELATIONSHIP BETWEEN RANDOM BLOOD SUGAR LEVELS AND SLEEP QUALITY OF ELDERLY PEOPLE WITH DIABETES MELLITUS AT THE PURWOSARI COMMUNITY HEALTH CENTER - Alfaqih, Mohamad; Dwi Khoiriya, Devi; Pramesti, Adhe Anniza (Jurnal Keperawatan Universitas Jambi, 2026)
Background: Diabetes mellitus is a degenerative disease commonly experienced by the elderly and is characterized by elevated blood sugar levels above normal limits. Hyperglycemia can cause various complaints, one of which is sleep disturbances. Poor sleep quality in the elderly can worsen blood glucose control and reduce quality of life. This study aims to determine the relationship between random blood sugar levels and sleep quality in elderly with diabetes mellitus at Health center of Purwosari District. Method: This study used an observational analytical design with a cross-sectional approach. The population was all elderly people with diabetes mellitus at the Elderly Health at Purwosari Health Care Center, with a sample size of 33 respondents selected using accidental sampling. Random blood sugar levels were measured using a glucometer, while sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data were analyzed using the Spearman Rho correlation test. Result : The result of the study showed that most respondents had random blood sugar levels above the normal limit (>199 mg/dl) and poor sleep quality. The p-value was 0.000, meaning the significance value was <0.05. Meanwhile, the Correlation Coefficient value was 0.685. This means there is a positive relationship with a strong relationship. Conclucion:  High random blood sugar levels can cause various complaints such as frequent urination at night, thirst, tingling, and pain, which impact the quality of sleep in the elderly. In order to enhance the quality of life of the elderly, healthcare facilities must establish educational programs that underscore the significance of glycaemic control and sleep quality as interrelated factors.   Keyword : Random Blood Glucose, Sleep Quality, Elderly, Diabetes Mellitus